EKSPERIMENTASI PENDEKATAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK DAN PROBLEM BASED LEARNING PADA OPERASI BILANGAN BULAT DITINJAU DARI GAYA BELAJAR SISWA - Rohman, Nur (Jurnal Pembelajaran Matematika, 2013)
ABSTRACTThe objectives of this research are to investigate: (1) which learning approach among realistic mathematics learning, problem-based learning, and conventional learning result in the studentsâ better learning achievement; (2) which learning style among visual, auditory, and kinesthetic learning styles results in the studentsâ better achievement; (3)In each learning approach, which learning achievement is better among the students with the visual, auditory and kinesthetic learning styles, and (4)In each learning style, which learning achievement is better among the students with realistic mathematics learning, problem-based learning, and conventional learning.This research used the quasi-experimental research method. The population of the research was all of the students in Grade V of State Primary Schools in Dander sub-district, Bojonegoro regency in Academic Year 2012/2013. The samples of the research were taken by using the stratified random sampling technique.The hypotheses of the research were tested by using the unbalanced two-way analysis of variance.The results of the research are as follows: 1) The realistic mathematics learning results in the same learning achievement as the problem-based learning does, but both the realistic mathematics learning and the problem-based learning result in a better learning achievement than the conventional one does. 2) The students with the auditory learning style have a better learning achievement than those either with the visual learning style or with the kinesthetic learning style, but the students with the visual learning style have the same learning achievement as those with the kinesthetic learning style. 3)In the realistic mathematics learning, the students with the visual learning style have a better learning achievement than those with the kinesthetic learning style, but the students with the auditory learning style have the same learning achievement as those with the kinesthetic style. In the problem-based learning, the student with the auditory learning style have a better learning achievement than those with the kinesthetic learning style, but the students with the visual learning style have the same learning achievement as those with the kinesthetic learning style. In the conventional learning, the learning achievements of the students with the auditory, visual, and kinesthetic learning styles are similar. 4) In the group of students with the visual learning style, the students instructed with the three learning approaches have the same learning achievement. In the group of students with the auditory learning style, learning achievements of the students instructed with the realistic mathematics, the problem-based learning, and the conventional one are similar, but the students instructed with the problem-based learning have a better learning achievement than those instructed with the conventional one. In the kinesthetic learning style, the learning achievements of the students instructed with the auditory, visual, and kinesthetic learning styles are similar